O item porem em contextos diversos nos séculos XIII-XV : análise de condicionantes morfossintáticos para sua gramaticalização - Rosa, Adel Fernanda Lourenzi Franco (2010)
The present research examined the linguistic change path of the item porém from the Brazilian Portuguese language in texts from the 13th, 14th and 15th centuries and observed which factors could have been pointed out as triggers to this change. In order to achieve this goal, the item porém was exhaustively scanned in four pieces of written texts that were: Vidas de Santos de um Manuscrito Alcobacence - 13th-15th centuries; Virgeu de Consolaçon - 14th century end and 15th century beginning; Orto do Esposo - 15th century end; and Leal Conselheiro - 15th century. The item porém was originally used as an adverb with the textual-semantic values coming from its Latin etymon of "this way", "for this reason", "because of that" and has started to exercise the value of conjunction with an adverse meaning as it is used nowadays. In order to identify the period of time in which that change might have happened, we adopted the analysis of frequency studied by Bybee that is divided into token frequency - the one that refers to the number of occurrences of the item researched in the corpora - and the type frequency - the one that points out the functions exercised by the item studied. The specific objectives of this study were: a) studying the item porem in relation to the token and type frequencies (respectively the number of occurrences and what were the functions presented by the item into the selected texts); b) investigating the factors that have possibly represented the triggers for the gramaticalization of the item porém; c) analyzing the gramaticalization stage in which the item was until the 15th century. When the research was concluded, we observed that even though the explanatory value was predominant in the synchronies studied there was a significant number of negative contexts in which the negative item came before the item porém negating it, and contexts in which the item porem came after the causative, adversative and concessive clauses as well, and that was what favored an adversative interpretation for the studied item.